2013
DOI: 10.1002/ajp.22215
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge and perceptions of chimpanzees in Cantanhez National Park, Guinea‐Bissau

Abstract: Our study concerns local knowledge and perceptions of chimpanzees among farming communities within Cantanhez National Park, Guinea-Bissau. We submitted a survey questionnaire to 100 people living in four villages in the Park to enquire about their knowledge of chimpanzee ecology and human-chimpanzee interactions. Local farmers live in close contact with chimpanzees, consider them to be more similar to humans than any other species, and attribute special importance to them primarily due to expectations of touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 50 publications
4
26
1
Order By: Relevance
“…This result does not corroborate our prediction that elderly individuals have a higher LEK. This finding is also contrary to the results published in the literature [Sousa, 2010;Oliveira, 2011;Sousa et al, 2014;Melo et al, 2014]. According to the respondents, it is necessary to travel to the reserve to see blonde capuchins or to hear red-handed howler monkeys.…”
Section: Discussioncontrasting
confidence: 56%
“…This result does not corroborate our prediction that elderly individuals have a higher LEK. This finding is also contrary to the results published in the literature [Sousa, 2010;Oliveira, 2011;Sousa et al, 2014;Melo et al, 2014]. According to the respondents, it is necessary to travel to the reserve to see blonde capuchins or to hear red-handed howler monkeys.…”
Section: Discussioncontrasting
confidence: 56%
“…In the early 2000s, a tourism project was launched by a local NGO and the chimpanzee became firmly associated with the park, both for tourists and for local people. By 2007, ‘chimpanzee tourism’ had already raised considerable expectations among local people regarding the economic advantages that would supposedly flow into the area (Sousa et al ). In 2010 and 2011, tour guides were paid by tourists visiting the forests to observe chimpanzees.…”
Section: Portrayals Of ‘Fearless’ Chimpanzees In a ‘Greedy’ National mentioning
confidence: 99%
“…In LCNP, agricultural areas could provide food supplement, but chimpanzees always included wild plant foods in their diet (Duvall 2008;Hockings et al 2009;McLennan 2013;Nishida and Shigeo 1983;Sabater-Pí 1979;Sousa et al 2013;Tutin and Fernandez 1985). Cultivated species were harder to identify in fecal samples than in feeding remains because the consumption of most cultivated species often results in seedless fruit pulp, e.g., extracting juice from cashew fruits.…”
Section: Discussionmentioning
confidence: 97%
“…We relied on local knowledge in our study when implementing the phenological surveys (Sousa et al 2013), and about half of the species matched with those species identified in fecal samples. Park guards and residents mentioned that chimpanzees in the dry season come closer to agricultural fields and cashew plantations than in the wet season.…”
Section: Discussionmentioning
confidence: 99%